2017
DOI: 10.4025/actascibiolsci.v39i4.36223
|View full text |Cite
|
Sign up to set email alerts
|

<b>Petroleum biodegrading and co-resistance to antibiotics by <i>Serratia marcescens</i> strain isolated in Coari, Amazonas

Abstract: ABSTRACT. Serratia marcescens is a Gram-negative bacillus, anaerobic facultative belonging to the family Enterobacteriaceae. S. marcescens strains are able to grow in the presence of different xenobiotic compounds, among them, petroleum and heavy metals. Xenobiotic resistant strains develop concomitant resistance to multiple antibiotics, referred to as co-resistance. The AMS212 strain was submitted to the microplate qualitative DCPIP -redox 2,6 dichlorophenol indophenol method. The quantitative test was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…The microbial culture was standardized at a wavelength of 600nm (10 9 cells/mL), cell density O.D = 1.0. The experiment was carried out as described by Hanson et al (1993), Peixoto et al (2017 and Peixoto et al (2018).…”
Section: Biodegradation Assay Using Dcpipmentioning
confidence: 99%
“…The microbial culture was standardized at a wavelength of 600nm (10 9 cells/mL), cell density O.D = 1.0. The experiment was carried out as described by Hanson et al (1993), Peixoto et al (2017 and Peixoto et al (2018).…”
Section: Biodegradation Assay Using Dcpipmentioning
confidence: 99%
“…The rod-shaped Gram-negative enteric bacterium Serratia marcescens has been reported to metabolize different polycyclic aromatic hydrocarbons (PAHs), heavy metals, and antibiotics ( 1 ). S. marcescens SSA1 was discovered in a screen for dioxin-degrading bacteria in dibenzofuran-rich soil obtained from an industrial waste dump site that had been repeatedly burned ( 2 ).…”
Section: Announcementmentioning
confidence: 99%
“…In addition, the lipases are known for their ability in the industry of oil and lipid processing, detergent production, and biotransformation (García-Silvera et al, 2018;Zied et al, 2018). Some studies have shown some applicability for S. marcescens lipase, such as petroleum biodegradation regenerating contaminated areas, generation of emulsifiers from cheap vegetable oils, and biodiesel production (García-Silvera et al, 2018;Peixoto et al, 2017;Zied et al, 2018).…”
Section: Genes Involved In Antimicrobial Activities or Important Enzymes For Industrymentioning
confidence: 99%